2016
DOI: 10.1007/s11745-016-4222-1
|View full text |Cite
|
Sign up to set email alerts
|

Eicosapentaenoic Acid‐Enriched Phosphatidylcholine Attenuated Hepatic Steatosis Through Regulation of Cholesterol Metabolism in Rats with Nonalcoholic Fatty Liver Disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disease in the world. Disturbed cholesterol metabolism plays a crucial role in the development of NAFLD. The present study was conducted to evaluate the effects of EPA-PC extracted from sea cucumber on liver steatosis and cholesterol metabolism in NAFLD. Male Wistar rats were randomly divided into seven groups (normal control group, model group, lovastatin group, low- and high-dose EPA groups, and low- and high-dose EPA-PC groups). Model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…Activities of AST and ALT in OA-induced NAFLD rats increased about onefold and twofold ( p < 0.01), respectively, compared with the control group, indicating that rats fed with OA diet displayed severe NAFLD with liver injury. Those results were in agreement with our previous studies [ 4 , 34 ].
Figure 2.
…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Activities of AST and ALT in OA-induced NAFLD rats increased about onefold and twofold ( p < 0.01), respectively, compared with the control group, indicating that rats fed with OA diet displayed severe NAFLD with liver injury. Those results were in agreement with our previous studies [ 4 , 34 ].
Figure 2.
…”
Section: Resultssupporting
confidence: 94%
“…In another study, Liu et al . [ 4 ] also found EPA-PL from C. frondosas had protective effects against NAFLD [ 4 ]. However, SCS treatment for 10 days could only significantly reduce hepatic TC content, and the TG content was slightly decreased without remarkable difference.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…EPA‐enriched phosphatidylcholine (EPA‐PC) has been reported to mediate lipid metabolism, and it was therefore used as a reference in the present study. [ 14,15 ] The results of our study indicated that EPA‐PlsEtns significantly reduced serum and hepatic lipid levels via facilitating fatty acid β‐oxidation and by increasing cholesterol efflux and the synthesis of bile acids.…”
Section: Introductionmentioning
confidence: 81%
“…Fish oils, mainly eicosapentaenoic acid (EPA) and docosahexanoic acid (DHA), represent one of the most highly marketed and widely used supplement types for many metabolic conditions [ 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 ]. They can improve lipid homeostasis and inflammation through the PPARα, AMPK, and adiponectin [ 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 ]. A 41-patient NASH study by Argo et al randomized patients to receive 3000 mg/day of fish oil or placebo for 1 year and observed improved ALT in the treated patients [ 140 ].…”
Section: Non-herb Supplementsmentioning
confidence: 99%